Empowering rural communities through asset-based community development: evidence from east java’s desa berdaya program - Ainun Ma’rifah; Nuphanudin Nuphanudin (Jurnal Konseling dan Pendidikan, 2025)
This study examines the implementation and outcomes of East Java’s Desa Berdaya (Empowered Village) program through the lens of the Sustainable Development Goals (SDGs), with a focus on poverty alleviation (SDG 1). Employing a qualitative case study approach and grounded in Asset-Based Community Development (ABCD) theory, we analyze two villages—Ketapanrame (tourism) and Sidoharjo (maggot farming). Findings reveal that village economic branding successfully leverages local assets, enhances community welfare, and fosters independence. However, sustainability challenges such as fluctuating tourist visits and land constraints threaten long-term impact. The study contributes to the literature on community-driven development and offers policy insights for scaling locally-grounded SDG initiatives in emerging economies